Vecuronium in tuberculosis: a rare case report of reversible quadriparesis - Kumar, Amarjeet; Kumar, Neeraj; Sinha, Chandni; Kirti, Ravi; Kumar, Sanjeev (DiscoverSys Inc., 2019)
ABSTRACTTuberculosis is a major health burden worldwide. The National treatment regimens for tuberculosis (TB) patients recommend the use of the five first lines anti TB drugs: isoniazid (INH), rifampicin (R), ethambutol (E), pyrazinamide (P) and streptomycin (S). Maintaining of oxygenation are very much challenging in tuberculosis patients associated with Acute Respiratory Distress Syndrome (ARDS). Often we need muscle relaxation with adequate sedation for maintaining oxygen saturation and lung recruitment. Skeletal muscle weakness has a confusing list of names and syndromes, including Acute Quadriplegic Myopathy Syndrome (AQMS), floppy man syndrome, critical illness polyneuropathy (CIP), and acute myopathy of intensive care. In disseminated tuberculosis with ARDS, we recommend the use of short-acting muscle relaxant drugs like cisatracurium whose metabolism not depends upon the liver. Interrupting the vecuronium infusion (vecuronium holiday) as its action was potentiated by streptomycin and corticosteroid which may result in the development of Critical Illness Polyneuro Myopathy (CIPM). Targeting Train of Four (TOF) of two rather than zero of four has been shown to be beneficial for a period of fewer than 48 hours.